Secondary batteries, power consumption devices
Patent Information
- Application Number
- JP2025526795
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-01-12
- Filing Date
- 2024-11-01
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-11-01
Smart Images

Figure 0007934037000004 
Figure 0007934037000005 
Figure 0007934037000006
Abstract
Description
[Technical Field]
[0001] cross reference This application claims priority to a Chinese invention patent application filed on January 12, 2024, with application number 202410046330.8 and the title of the invention "Secondary Battery, Power Consumption Device," the contents of which are incorporated herein by reference.
[0002] Technical field This application relates to a secondary battery and a power consumption device. [Background technology]
[0003] In recent years, with the advancement of lithium-ion secondary battery technology, lithium-ion secondary batteries are widely used in energy storage and power systems such as hydroelectric, thermal, wind, and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. Due to their remarkable development, lithium-ion secondary batteries are now required to have higher energy density and rapid charging performance. [Overview of the project]
[0004] The purpose of this application is to provide a secondary battery and a power consumption device.
[0005] The embodiment of this application is realized as follows.
[0006] According to a first aspect, an embodiment of the present application provides a secondary battery including a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer including a lower region and an upper region, the lower region including a first negative electrode active material, the upper region including a second negative electrode active material, and the median of the Raman values ID / IG of the first negative electrode active material being R1 50 It is noted that the median of the Raman values ID / IG of the second negative electrode active material is R2 50 The above R1 50 R2 50The degree of graphitization of the first negative electrode active material is smaller than that of the second negative electrode active material.
[0007] The above proposed technology achieves both improved rapid charging performance and improved energy density of lithium-ion batteries by controlling the median Raman value ID / IG of the first negative electrode active material in the negative electrode film layer close to the negative electrode current collector (i.e., the lower region) to be relatively low, the median Raman value ID / IG of the second negative electrode active material in the negative electrode film layer further away from the negative electrode current collector (i.e., the upper region) to be relatively high, and the degree of graphitization of the first negative electrode active material to be greater than that of the second negative electrode active material.
[0008] In some selective implementation plans, R1 50 The range is 0.05 to 0.15, and selectively, R1 50 is 0.05 to 0.1, and / or R2 50 The range is 0.20 to 0.40, and selectively, R2 50 The range is 0.25 to 0.35.
[0009] The above proposed technology allows for synergistic cooperation by controlling the median Raman value ID / IG of the first negative electrode active material in the negative electrode film layer close to the negative electrode current collector to be relatively low, and the median Raman value ID / IG of the second negative electrode active material in the negative electrode film layer further away from the negative electrode current collector to be relatively high. This enables improvement in the rapid charging performance of lithium-ion batteries while simultaneously improving the energy density of lithium-ion batteries.
[0010] In some selective implementations, the degree of graphitization of the first negative electrode active material is ≥92%, selectively 93%~95%, and / or The degree of graphitization of the second negative electrode active material is ≥91%, and selectively between 92% and 94%.
[0011] In the above technical solution, the graphitization degree of the first negative electrode active material is greater than the graphitization degree of the second negative electrode active material, or falls within the above range, which is advantageous for improving the energy density of the lithium-ion battery, and at the same time advantageous for improving the fast charging performance of the lithium-ion battery.
[0012] In some optional embodiments, the powder compaction density of the first negative electrode active material is greater than the powder compaction density of the second negative electrode active material.
[0013] In some optional embodiments, the powder compaction density of the first negative electrode active material tested under a pressure of 49000N is ≧1.95g / cm 3 , and optionally 1.96g / cm 3 ~1.99g / cm 3 , and / or the powder compaction density of the second negative electrode active material tested under a pressure of 49000N is 1.81g / cm 3 ~1.87g / cm 3 , and optionally 1.82g / cm 3 ~1.86g / cm 3 .
[0014] In the above technical solution, by setting the powder compaction density of the first negative electrode active material to be greater than the powder compaction density of the second negative electrode active material, or to fall within the above range, the improvement of the fast charging performance of the lithium-ion battery can be realized, and at the same time, the improvement of the energy density of the lithium-ion battery can be achieved at the same time.
[0015] In some optional embodiments, the powder OI of the first negative electrode active material is greater than the powder OI of the second negative electrode active material.
[0016] In some optional embodiments, the powder OI of the first negative electrode active material is 2.0~10.0, optionally 4.0~8.0, and / or the powder OI of the second negative electrode active material is 1.0~8.0, optionally 2.5~5.5.
[0017] The above-described technical proposal is advantageous in improving the energy density of a lithium-ion battery, and at the same time, in improving the rapid charging performance of a lithium-ion battery, because the powder OI of the first negative electrode active material is greater than or within the above range than the powder OI of the second negative electrode active material.
[0018] In some selective implementations, the tap density of the first negative electrode active material is smaller than that of the second negative electrode active material.
[0019] In some selective implementations, the tap density of the first negative electrode active material is ≥ 0.8 g / cm³. 3 Therefore, selectively 0.9 g / cm³ 3 ~1.1 g / cm³ 3 and / or, The specific surface area of the second negative electrode active material is 3.0 m². 2 / g~4.3m 2 It is / g, and selectively 3.2m 2 / g~4.0m 2 It is / g.
[0020] The above-described technical proposal is advantageous in that the tap density of the first negative electrode active material is smaller than or within the above range than the tap density of the second negative electrode active material, thereby further improving the energy density of the lithium-ion battery and simultaneously improving the rapid charging performance of the lithium-ion battery.
[0021] In some selective implementations, the volume-distributed particle size Dv1 of the first anode active material is smaller than the volume-distributed particle size Dv1 of the second anode active material.
[0022] In some selective implementations, the volume distribution particle size Dv1 of the first negative electrode active material is 1.0 μm to 8.0 μm, selectively 3.0 μm to 5.0 μm, and / or The volume distribution particle size Dv1 of the second negative electrode active material is 3.5 μm to 10.0 μm, and selectively 5.5 μm to 8.0 μm.
[0023] In some selective implementations, the volume-distributed particle size Dv50 of the first anode active material is larger than the volume-distributed particle size Dv50 of the second anode active material.
[0024] In some selective implementations, the volume distribution particle size Dv50 of the first negative electrode active material is 10 μm to 20 μm, and selectively 15 μm to 16.5 μm. The volume distribution particle size Dv50 of the second negative electrode active material is 10 μm to 20 μm, and selectively 13 μm to 14.5 μm.
[0025] In some selective implementations, the particle size distribution of the first negative electrode active material (D V 90-D V 10) / D V 50 is the particle size distribution of the second negative electrode active material (D V 90-D V 10) / D V It's larger than 50.
[0026] In some selective implementations, the particle size distribution of the first negative electrode active material (D V 90-D V 10) / D V 50 is ≤2.0, and selectively between 1.2 and 1.8. Particle size distribution of the second negative electrode active material (D V 90-D V 10) / D V 50 is ≤ 1.8, and selectively between 1.0 and 1.6.
[0027] The above technical proposal concerns the particle size distribution (D) of the first negative electrode active material. V 90-D V 10) / D V 50 is the particle size distribution of the second negative electrode active material (D V 90-D V 10) / D V Setting the value greater than 50 allows for the formation of a good normal distribution of particle size, which is advantageous for improving the energy density of lithium-ion batteries and simultaneously for improving the rapid charging performance of lithium-ion batteries.
[0028] In some selective implementations, the specific surface area of the first negative electrode active material is smaller than that of the second negative electrode active material.
[0029] In some selective implementations, the specific surface area of the first negative electrode active material is 0.5 m². 2 / g~3.0m 2 It is / g, and selectively 1.0m 2 / g~2.5m 2 / g and / or The specific surface area of the second negative electrode active material is 2.5 m². 2 / g~4.4m 2 It is / g, and selectively 3.0m 2 / g~4.0m 2 It is / g.
[0030] In some selective implementations, the first negative electrode active material is (1) D of the first negative electrode active material V The characteristic of 10 is that it is 5 μm to 9 μm, and selectively 5.8 μm to 7.8 μm, (2) D of the first negative electrode active material V The characteristic is that it is 90 ≤ 30 μm, and selectively 20 μm to 30 μm, (3) D of the first negative electrode active material V The characteristic is that it is 99 ≤ 40 μm, and selectively 30 μm to 40 μm, (4) The gram capacity of the first negative electrode active material is 355 mAh / g to 365 mAh / g, and selectively 357 mAh / g to 363 mAh / g, satisfying at least one of these characteristics.
[0031] In some selective implementations, the second negative electrode active material is (1) D of the second negative electrode active material V The characteristic is that 10 is 6 μm to 10.0 μm, and selectively 7.5 μm to 9.0 μm, (2) D of the second negative electrode active material V The characteristic is that it is 90 ≤ 30 μm, and selectively 20 μm to 30 μm, (3) D of the second negative electrode active material V The characteristic is that it is 99 ≤ 40 μm, and selectively 30 μm to 40 μm, (4) The second negative electrode active material has a gram capacity of 352 mAh / g to 362 mAh / g, and is selectively 354 mAh / g to 360 mAh / g, (5) The second negative electrode active material satisfies at least one of the following characteristics: at least a portion of its surface has a carbon coating layer.
[0032] In some selective implementations, the first and / or second anode active materials are both artificial graphite.
[0033] In some selective implementations, the compaction density of the negative electrode film layer is 1.25 g / cm³. 3 The above is the result, and selectively 1.28 g / cm³ 3 ~1.65g / cm 3 and / or, The coating weight per unit area of the negative electrode film layer is 0.075 mg / mm². 2 The above is the result, and selectively 0.08 mg / mm³ 2 ~0.11 mg / mm³ 2 That is the case.
[0034] According to a second aspect, an embodiment of the present application provides a power consumption device including a secondary battery according to the first aspect. [Brief explanation of the drawing]
[0035] To more clearly illustrate the technical concepts of the embodiments of this application, the following drawings are briefly presented as necessary for use in the embodiments. However, it should be understood that these drawings only illustrate some embodiments of this application and should not be considered as limitations on the scope. Those skilled in the art can, without expending any creative effort, obtain other relevant drawings based on these.
[0036] [Figure 1] This is a schematic diagram of one embodiment of the negative electrode plate of the present application. [Figure 2] This is a schematic diagram of another embodiment of the negative electrode plate of this application. [Figure 3] This is a schematic diagram of yet another embodiment of the negative electrode plate of this application. [Figure 4] This is a schematic diagram of a battery cell according to one embodiment of the present application. [Figure 5] Figure 4 is an exploded view of a battery cell according to one embodiment of this application. [Figure 6] This is a schematic diagram of a battery module according to one embodiment of the present application. [Figure 7] This is a schematic diagram of a battery pack according to one embodiment of the present application. [Figure 8] Figure 7 is an exploded view of a battery pack according to one embodiment of this application. [Figure 9] This is a schematic diagram of a power consumption device powered by a secondary battery according to one embodiment of the present application. [Modes for carrying out the invention]
[0037] The embodiments specifically disclosing the secondary battery and electrical device of this application will be described in detail below, with appropriate reference to the drawings. However, unnecessary detailed explanations may be omitted. For example, detailed explanations of well-known matters and repeated explanations of structures that are actually the same may be omitted. This is to avoid the following explanation becoming unnecessarily verbose and to make it easily understandable to those skilled in the art. The drawings and the following explanation are provided to enable those skilled in the art to fully understand this application and are not intended to limit the gist of the claims.
[0038] The “range” disclosed in this application is limited in the form of a lower limit and an upper limit, and a given range is limited by selecting one lower limit and one upper limit, which define the boundary of a particular range. The range thus limited may or may not include the limit value, and any combination is possible, that is, any lower limit may be combined with any upper limit to form a range. For example, if the ranges 60-120 and 80-110 are listed for a particular parameter, it is understood that the ranges 60-110 and 80-120 can also be assumed. Furthermore, if 1 and 2 are listed as the minimum range values and 3, 4, and 5 are listed as the maximum range values, then the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 can all be assumed. In this application, unless otherwise specified, the numerical range “a-b” represents an abbreviated expression of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0 to 5" indicates that all real numbers between "0 to 5" have already been listed in this specification, and "0 to 5" is merely a shortened representation of combinations of these numbers. Also, expressing a parameter as an integer ≥ 2 is equivalent to disclosing that this parameter is an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0039] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical inventions.
[0040] Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical concepts.
[0041] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, but preferably sequentially. For example, the fact that the method includes steps (a) and (b) means that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the fact that the method referred to above may further include step (c) means that step (c) may be added to the method in any order, for example the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), and so on.
[0042] The negative electrode has a certain influence on the energy density and rapid charging capability of the battery. Surprisingly, we discovered that by controlling the negative electrode according to this application, it is possible to obtain a secondary battery that simultaneously possesses both high energy density and rapid charging capabilities.
[0043] Based on this, a first aspect of this application provides a secondary battery that can achieve both improved rapid charging performance and improved energy density.
[0044] As used herein, “rechargeable battery” refers to a battery cell, battery module, or battery pack.
[0045] A typical secondary battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions intermittently
[0046] [Negative electrode plate] The secondary battery includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector.
[0047] The negative electrode film layer has a first surface adjacent to the negative electrode current collector and a second surface positioned opposite the first surface. The negative electrode film layer has a lower region in which it extends from the first surface to a certain thickness in the thickness direction, and an upper region in which it extends from the second surface to a certain thickness in the thickness direction.
[0048] Let H be the thickness of the negative electrode film layer. The thickness of the lower region can be any value within the range of 0.1H to 0.9H. For example, the thickness of the lower region can be 0.1H, 0.2H, 0.3H, 0.4H, 0.5H, 0.6H, 0.7H, 0.8H, or 0.9H.
[0049] The thickness of the upper region can be any value within the range of 0.1H to 0.9H. For example, the thickness of the upper region can be 0.1H, 0.2H, 0.3H, 0.4H, 0.5H, 0.6H, 0.7H, 0.8H, or 0.9H.
[0050] Selectively, the negative electrode film layer further includes an intermediate region.
[0051] Referring to Figures 1 to 3, schematic diagrams of several different specific embodiments of the negative electrode plate of this application are shown here. As shown in Figures 1 to 3, the negative electrode plate 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101, wherein the negative electrode film layer 102 has a first surface 102b adjacent to the negative electrode current collector 101 and a second surface 102a positioned opposite the first surface 102b, and the thickness of the negative electrode film layer 102 is denoted as H. The thickness H of the negative electrode film layer is the thickness of the negative electrode film layer located on one side of the negative electrode current collector. The region from the second surface 102a of the negative electrode film layer to a certain thickness range (e.g., 0.3H) is denoted as the upper region 1022 of the negative electrode film layer. The region from the first surface 102b of the negative electrode film layer to a certain thickness range (e.g., 0.3H) is denoted as the lower region 1021 of the negative electrode film layer. The lower region 1021 contains the first negative electrode active material, and the upper region 1022 contains the second negative electrode active material. The region between the upper region 1022 and the lower region 1021, occupying a thickness of 0.4H, is referred to as the intermediate region 1023. For ease of understanding, as shown in Figures 1 to 3, the intermediate region 1023 may contain only the first negative electrode active material, only the second negative electrode active material, or both the first and second negative electrode active materials simultaneously.
[0052] It should be understood that, in the embodiments shown in Figures 1 to 3, the first surface 102b is in contact with the upper surface of the negative electrode current collector 101, but the structure of the negative electrode plate in this application is not limited to this. For example, there may be an additional layer between the negative electrode film layer 102 and the negative electrode current collector 101. In this case, the first surface 102b does not directly contact the negative electrode current collector 101.
[0053] Specifically, Figures 1 to 3 show that the first negative electrode active material and the second negative electrode active material are sequentially coated onto the negative electrode current collector 101. Figure 1 shows that the thickness of the lower region and the upper region each account for approximately half the thickness of the negative electrode film layer 102. Figure 2 shows that the thickness of the upper region accounts for approximately 30% of the thickness of the negative electrode film layer 102, and the thickness of the lower region accounts for approximately 70% of the thickness of the negative electrode film layer 102. Figure 3 shows the opposite configuration to Figure 2, namely that the thickness of the lower region accounts for approximately 30% of the thickness of the negative electrode film layer 102, and the thickness of the upper region accounts for approximately 70% of the thickness of the negative electrode film layer 102.
[0054] It should be understood that Figures 1 to 3 are schematic diagrams of an ideal situation. This application does not particularly limit the ratio of the thicknesses of the lower region to the upper region; for example, they can be any ratio in the range of 1:9 to 9:1. Exemplary examples include the ratio of the thicknesses of the lower region to the upper region being 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, or any ratio between any two of these ratios.
[0055] Furthermore, it should be understood that while Figures 1 through 3 show clear boundaries between regions, products may not have such clear interfaces.
[0056] In this application, the median of the Raman values ID / IG of the first negative electrode active material is R1 50 It is noted that the median of the Raman values ID / IG of the second negative electrode active material is R2 50 It was written, R1 50 R2 50 It is smaller than [value]. In the above technical proposal, the median Raman value ID / IG represents the degree of disorder across the entire material surface. A smaller median Raman value ID / IG indicates a lower degree of disorder across the entire material surface, and a smaller median Raman value ID / IG for a material is favorable for energy density.
[0057] In some embodiments of this application, the first negative electrode active material may be selected from highly anisotropic raw materials or materials with a high degree of graphitization produced by a high-temperature graphitization process, and exemplary may be selected from needle-shaped coke graphite fluorinated rings, petroleum coke graphite fluorinated rings, etc.
[0058] In some embodiments of this application, the second anode active material may be a graphite material with a relatively high degree of disorder to obtain a second anode active material with a relatively large median Raman value ID / IG. More selectively, the second anode active material may be manufactured by a process that applies a highly disordered coating layer to the graphite, and may be obtained, for example, by applying a hard carbon coating layer to the graphite.
[0059] Furthermore, in the above proposed technology, the median Raman value ID / IG of the first negative electrode active material in the lower region is relatively low, which is advantageous for the energy density of the battery.
[0060] Furthermore, a larger median Raman value (ID / IG) indicates a greater degree of disorder across the entire material surface. A greater degree of disorder is favorable for ion charge exchange on the surface of the negative electrode active material.
[0061] In the above proposed technology, the median Raman value ID / IG of the second negative electrode active material in the upper region is relatively high, which is advantageous for charge exchange on the surface of the negative electrode active material, and thereby is advantageous for improving dynamic performance.
[0062] Furthermore, in some embodiments of this application, the median Raman value ID / IG of the second negative electrode active material is not only greater but also more uniformly distributed. This is further advantageous for lithium ion transfer and for kinetic performance.
[0063] Furthermore, in some embodiments of this application, the degree of graphitization of the first negative electrode active material is greater than that of the second negative electrode active material.
[0064] This application aims to improve the rapid charging performance of lithium-ion batteries while simultaneously improving the energy density of lithium-ion batteries by controlling the median Raman value ID / IG of the first negative electrode active material in the lower region to be relatively low, the median Raman value ID / IG of the second negative electrode active material in the upper region to be relatively high, and the degree of graphitization of the first negative electrode active material to be greater than the degree of graphitization of the second negative electrode active material.
[0065] Furthermore, in some embodiments of this application, the above R1 50 The range is 0.05 to 0.15.
[0066] More selectively and exemplary, in some embodiments of this application, the above R1 50 This range is 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or any two of the aforementioned numbers.
[0067] In the above technical proposal, R1 50 By setting it to 0.05~0.15, the aforementioned R2 50 This allows for matching with lithium-ion batteries, improving their rapid charging performance while simultaneously increasing their energy density.
[0068] Furthermore, selectively, in some embodiments of this application, the above R1 50 The range is 0.05 to 0.10.
[0069] Exemplary, in some embodiments of this application, the above R1 50 These values are 0.05, 0.06, 0.07, 0.08, 0.09, or 0.10.
[0070] The above technical proposal further includes R1 50 Limiting the value to the range of 0.05 to 0.10 is even more advantageous in simultaneously improving the rapid charging performance of lithium-ion batteries and increasing their energy density.
[0071] Furthermore, in some embodiments of this application, R2 50 The range is 0.20 to 0.40.
[0072] Exemplary, in some embodiments of this application, the above R2 50 is a range between 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.28, 0.30, 0.35, 0.38, 0.39, 0.40, or any two of the numbers mentioned above.
[0073] In the above technical proposal, R2 50 By setting R1 to 0.20~0.40, 50 This allows for matching with lithium-ion batteries, improving their rapid charging performance while simultaneously increasing their energy density.
[0074] Furthermore, selectively, in some embodiments of this application, R2 50 The range is 0.25 to 0.35.
[0075] For example, R2 50 These values are 0.25, 0.26, 0.28, 0.31, 0.32, or 0.35.
[0076] The above technical proposal further includes R2 50 Limiting the value to the range of 0.25 to 0.35 is even more advantageous in simultaneously improving the rapid charging performance of lithium-ion batteries and increasing their energy density.
[0077] Furthermore, in some embodiments of this application, the degree of graphitization of the first negative electrode active material is ≥92%, and selectively 93-95%.
[0078] In the above proposed technology, by setting the degree of graphitization of the first negative electrode active material to ≥ 94%, the energy density of the lithium-ion battery can be further improved effectively, and at the same time, it is advantageous for improving the rapid charging performance of the lithium-ion battery.
[0079] More selectively, in some selective embodiments of this application, the degree of graphitization of the first negative electrode active material is in the range of 92%, 93%, 94%, 95%, or any two of the aforementioned values.
[0080] Furthermore, in some embodiments of this application, the degree of graphitization of the second negative electrode active material is ≥91%, and selectively 92-94%.
[0081] In the above proposed technology, by setting the degree of graphitization of the second negative electrode active material to ≥ 91%, the energy density of the lithium-ion battery can be further improved effectively, and at the same time, it is advantageous for improving the rapid charging performance of the lithium-ion battery.
[0082] More selectively, in some selective embodiments of this application, the degree of graphitization of the second negative electrode active material is in the range of 91%, 92%, 93%, 94%, or any two of the aforementioned values.
[0083] Furthermore, in some embodiments of this application, the powder compaction density of the first negative electrode active material is greater than the powder compaction density of the second negative electrode active material.
[0084] The fact that the powder compaction density of the first negative electrode active material is greater than that of the second negative electrode active material indicates that the compaction density is higher in the lower region of the negative electrode film layer and lower in the upper region of the negative electrode film layer. As a result, particle deposition is densely concentrated in the lower region of the negative electrode film layer, fully exhibiting the high-pressure, high-density, and high-capacity characteristics of the active material and ensuring the energy density of the film layer. The upper region of the negative electrode film layer, having a relatively low compaction density, has abundant voids, providing sufficient pathways for lithium ion transfer within the electrode plate and ensuring the rapid charging capability of the film layer.
[0085] In the above technical solution, by setting the powder compaction density of the first negative electrode active material to be greater than the powder compaction density of the second negative electrode active material, the rapid charging performance of the lithium-ion battery can be improved, and at the same time, the energy density of the lithium-ion battery can be improved in a compatible manner.
[0086] Further, in some embodiments of the present application, the first negative electrode active material has a powder compaction density tested under a pressure of 49000N of ≧1.95g / cm 3 , and optionally 1.96g / cm 3 ~1.99g / cm 3 .
[0087] Illustratively, in some embodiments of the present application, the first negative electrode active material has a powder compaction density tested under a pressure of 49000N of 1.96g / cm 3 , 1.97g / cm 3 , 1.98g / cm 3 , 1.99g / cm 3 .
[0088] Further, in some embodiments of the present application, the second negative electrode active material has a powder compaction density tested under a pressure of 49000N of 1.81g / cm 3 ~1.87g / cm 3 , and optionally 1.82g / cm 3 ~1.86g / cm 3 .
[0089] Illustratively, in some embodiments of the present application, the second negative electrode active material has a powder compaction density tested under a pressure of 49000N of 1.81g / cm 3 , 1.82g / cm 3 , 1.83g / cm 3 , 1.84g / cm 3 , 1.85g / cm 3 or 1.86g / cm 3 .
[0090] Further, in some embodiments of the present application, the powder OI of the first negative electrode active material is greater than the powder OI of the second negative electrode active material.
[0091] Further, in some embodiments of the present application, the OI of the first negative electrode active material is 4.0 to 8.0.
[0092] In some embodiments of the present application, the powder OI of the second negative electrode active material is 1.0 to 8.0.
[0093] The OI in the above technical solutions refers to the voltage of the first or second negative electrode active material during the discharge process. The OI value of the first or second negative electrode active material directly affects the energy density of the lithium-ion battery.
[0094] In the above technical solutions, by setting the OI of the first negative electrode active material to 4.0 to 8.0 and setting the powder OI of the second negative electrode active material to 1.0 to 8.0, it is beneficial to improving the energy density of the lithium-ion battery, and at the same time, it is beneficial to improving the fast charging performance of the lithium-ion battery.
[0095] Exemplarily, in some embodiments of the present application, the OI of the aforementioned first negative electrode active material is 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, or a range between any two of the aforementioned numerical values.
[0096] Exemplarily, in some embodiments of the present application, the OI of the aforementioned second negative electrode active material is 1.0, 2.0, 3.0, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, or a range between any two of the aforementioned numerical values.
[0097] Further, in some embodiments of the present application, the tap density of the first negative electrode active material is smaller than the tap density of the second negative electrode active material.
[0098] Further, in some embodiments of the present application, the tap density of the first negative electrode active material is ≧0.8g / cm 3 , and optionally 0.9g / cm 3 ~1.1g / cm 3 .
[0099] Furthermore, in some embodiments of this application, the specific surface area of the second negative electrode active material is 3.0 m². 2 / g~4.3m 2 It is / g, and selectively 3.2m 2 / g~4.0m 2 It is / g.
[0100] Furthermore, in the above proposed technology, by setting the tap density of the first or second negative electrode active material within the above range, the energy density of the lithium-ion battery can be effectively improved, and at the same time, it is advantageous in improving the rapid charging performance of the lithium-ion battery.
[0101] Exemplary, in some embodiments of this application, the tap density of the first negative electrode active material is 0.9 g / cm³. 3 , 1 g / cm³ 3 Or 1.1 g / cm³ 3 The specific surface area of the second negative electrode active material is 3.0 m². 2 / g, 3.2m 2 / g, 3.5m 2 / g, 3.8m 2 / g or 4.0m 2 It is / g.
[0102] Furthermore, in some embodiments of this application, the volume-distributed particle size Dv1 of the first negative electrode active material is smaller than the volume-distributed particle size Dv1 of the second negative electrode active material.
[0103] Furthermore, in some embodiments of this application, the volume distribution particle size Dv1 of the first negative electrode active material is 1.0 μm to 8.0 μm, and selectively 3.0 μm to 5.0 μm.
[0104] Furthermore, in some embodiments of this application, the volume distribution particle size Dv1 of the second negative electrode active material is 3.5 μm to 10.0 μm, and selectively 5.5 μm to 8.0 μm.
[0105] Exemplary, in some embodiments of this application, the volume-distributed particle size Dv1 of the first negative electrode active material is 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, or 8.0 μm, and the volume-distributed particle size Dv1 of the second negative electrode active material is 3.5 μm, 3.8 μm, 4 μm, 4.5 μm, 6 μm, 8 μm, or 10.0 μm.
[0106] Furthermore, in some embodiments of this application, the volume-distributed particle size Dv50 of the first negative electrode active material is larger than the volume-distributed particle size Dv50 of the second negative electrode active material.
[0107] Furthermore, in some embodiments of this application, the volume distribution particle size Dv50 of the first negative electrode active material is 10 μm to 20 μm, and selectively 15 μm to 16.5 μm.
[0108] Furthermore, in some embodiments of this application, the volume distribution particle size Dv50 of the second negative electrode active material is 10 μm to 20 μm, and selectively 13 μm to 14.5 μm.
[0109] Furthermore, exemplary, in some embodiments of this application, the D of the first negative electrode active material described above V 50 is the range between 13.0 μm, 13.5 μm, 14.0 μm, 14.5 μm, 15.0 μm, 15.5 μm, 16.0 μm, 16.5 μm, 17.0 μm, or any two of the aforementioned values.
[0110] Furthermore, exemplary, in some embodiments of this application, the second negative electrode active material D V 50 is a range between 13.0 μm, 13.2 μm, 13.4 μm, 13.5 μm, 14.0 μm, 14.5 μm, or any two of the aforementioned values.
[0111] Furthermore, in some embodiments of this application, the particle size distribution (D) of the first negative electrode active material is also expressed. V 90-D V 10) / D V 50 is the particle size distribution of the second negative electrode active material (D V 90-D V 10) / D VIt's larger than 50.
[0112] Furthermore, in some embodiments of this application, the particle size distribution (D) of the first negative electrode active material is also expressed. V 90-D V 10) / D V 50 is ≤2.0, and selectively between 1.2 and 1.8.
[0113] Furthermore, in some embodiments of this application, the particle size distribution (D) of the second negative electrode active material is also specified. V 90-D V 10) / D V 50 is ≤ 1.8, and selectively between 1.0 and 1.6.
[0114] In the above technical proposal, the first and second negative electrode active materials are (D V 90-D V 10) / D V By setting 50 within the above range, a good normal distribution of particle size can be formed, which is advantageous for improving the energy density of lithium-ion batteries and simultaneously advantageous for improving the rapid charging performance of lithium-ion batteries.
[0115] Exemplary, in some embodiments of this application, the first negative electrode active material is (D V 90-D V 10) / D V 50 is 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, or 1.8.
[0116] The second negative electrode active material (D V 90-D V 10) / D V 50 is a range between 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, or any two of the aforementioned numbers.
[0117] Furthermore, in some embodiments of this application, the specific surface area of the first negative electrode active material is smaller than the specific surface area of the second negative electrode active material.
[0118] Furthermore, in some embodiments of this application, the specific surface area of the first negative electrode active material is 0.5 m². 2 / g~3.0m 2 It is / g, and selectively 1.0m 2 / g~2.5m 2 It is / g.
[0119] Furthermore, in some embodiments of this application, the specific surface area of the second negative electrode active material is 2.5 m². 2 / g~4.4m 2 It is / g, and selectively 3.0m 2 / g~4.0m 2 It is / g.
[0120] Exemplary, in some embodiments of this application, the specific surface area of the first negative electrode active material is 0.5 m². 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g or 3.0m 2 The value is / g. The specific surface area of the second negative electrode active material is 2.5m². 2 / g, 2.8m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g or 4.4m 2 It is / g.
[0121] Furthermore, in the above proposed technology, the specific surface area of the first or second negative electrode active material is the specific surface area of the material measured when CO2 is used as the carrier gas. Since CO2 molecules are relatively small and can enter the micropore structure of the material, the CO2 adsorption specific surface area can reflect information such as the ratio of micropores in the material. When the CO2 adsorption specific surface area of the first negative electrode active material falls within the above range, it is possible to effectively improve the energy density of the lithium-ion battery and, at the same time, is advantageous in improving the rapid charging performance of the lithium-ion battery.
[0122] Furthermore, in some embodiments of this application, the first negative electrode active material is (1) D of the first negative electrode active materialV 10 is characterized by being 5 μm to 9 μm, and selectively 5.8 μm to 7.8 μm, (2) D of the first negative electrode active material V The characteristic is that it is 90 ≤ 30 μm, and selectively 20 μm to 30 μm, (3) D of the first negative electrode active material V The characteristic is that it is 99 ≤ 40 μm, and selectively 30 μm to 40 μm, (4) The gram capacity of the first negative electrode active material is 355 mAh / g to 365 mAh / g, and selectively satisfies at least one of the following characteristics:
[0123] Furthermore, in some embodiments of this application, the second negative electrode active material is (1) D of the second negative electrode active material V 10 is characterized by being 6 μm to 10.0 μm, and selectively 7.5 μm to 9.0 μm, (2) D of the second negative electrode active material V The characteristic is that it is 90 ≤ 30 μm, and selectively 20 μm to 30 μm, (3) D of the second negative electrode active material V The characteristic is that it is 99 ≤ 40 μm, and selectively 30 μm to 40 μm, (4) The gram capacity of the second negative electrode active material is 352 mAh / g to 362 mAh / g, and is selectively 354 mAh / g to 360 mAh / g, (5) At least a portion of the surface of the second negative electrode active material satisfies at least one of the following characteristics: having a carbon coating layer.
[0124] Furthermore, in the above proposed technology, by having the gram capacity of the first or second negative electrode active material within the above range, it is possible to effectively achieve both a relatively high energy density and good rapid charging performance in the battery.
[0125] Furthermore, in the above proposed technology, the initial Coulomb efficiency of the first or second negative electrode active material falls within the above range, which effectively improves the energy density of the lithium-ion battery and simultaneously enhances the rapid charging performance of the lithium-ion battery.
[0126] In the above proposed technology, the D of the first or second negative electrode active material V 10, D V 50, D V 90, D V 99, D V Setting 1 within the above range is advantageous for improving the energy density of lithium-ion batteries, and at the same time, it is advantageous for improving the rapid charging performance of lithium-ion batteries.
[0127] Furthermore, in some embodiments of this application, the first negative electrode active material and / or the second negative electrode active material are both artificial graphite.
[0128] Furthermore, in some embodiments of this application, the compaction density of the negative electrode film layer is 1.25 g / cm³. 3 The above is the result, and selectively 1.28 g / cm³ 3 ~1.65g / cm 3 That is the case.
[0129] Exemplary, in some embodiments of this application, the compaction density of the negative electrode film layer is 1.28 g / cm³. 3 1.3 g / cm³ 3 1.35 g / cm³ 3 1.4 g / cm³ 3 1.45 g / cm³ 3 1.5 g / cm³ 3 , 1.55 g / cm³ 3 1.6 g / cm³ 3 Or 1.65 g / cm³ 3 That is the case.
[0130] Furthermore, in some embodiments of this application, the coating weight per unit area of the negative electrode film layer is 0.075 mg / mm². 2 The above is the result, and selectively 0.08 mg / mm³ 2 ~0.11 mg / mm³ 2 That is the case.
[0131] Exemplary, in some embodiments of this application, the coating weight per unit area of the negative electrode film layer is 0.08 mg / mm². 2, 0.09 mg / mm³ 2 , 0.1 mg / mm 2 or 0.11 mg / mm³ 2 That is the case.
[0132] In some embodiments, the negative electrode film layer further selectively comprises a conductive agent. The conductive agent can be at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0133] In some embodiments, the negative electrode film layer further optionally comprises an adhesive. The adhesive can be at least one selected from styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0134] In some embodiments, the negative electrode film layer further selectively includes other additives, such as thickeners (e.g., sodium carboxymethylcellulose (CMC-Na)).
[0135] Where the above-mentioned conductive agents, adhesives, and other auxiliary agents are present, this application does not particularly limit their types or quantities, and a person skilled in the art can select and determine them according to their actual needs.
[0136] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, copper foil may be used as the metal foil sheet. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer material substrate (for example, a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE)).
[0137] In some embodiments, the negative electrode plate may be manufactured in the following manner: The above components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other component, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, the negative electrode slurry is applied onto a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.
[0138] The negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is installed on one or both of the two opposing surfaces of the negative electrode current collector. It should be noted that the parameters of each negative electrode film layer given in this application refer to the parameters of the negative electrode film layer on one side of the negative electrode current collector. If the negative electrode film layer is installed on both sides of the negative electrode current collector, it is considered to fall within the scope of protection of this application if the parameters of the negative electrode film layer on either side satisfy the requirements of this application.
[0139] This application does not exclude the possibility that the negative electrode plate may include other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate further includes a conductive undercoating (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and placed on the surface of the negative electrode current collector, and in some embodiments, the negative electrode plate further includes a protective layer covering the surface of the negative electrode film layer.
[0140] In this application, the ID / IG values of materials (e.g., first negative electrode active material, second negative electrode active material, etc.) can be tested using a Raman spectrometer, and the ID is 1350 ± 50 cm⁻¹. -1 This represents the D peak intensity of the Raman spectrum of the material at 1580±50 cm⁻¹, where IG is 1580±50 cm⁻¹. -1 This represents the G peak intensity of the Raman spectrum of the material. The test conditions can be as follows: the excitation wavelength is 532 nm, the grating has 600 markings, the objective lens is 50x, the integration time is 10 s, the number of integrations is 3, the surface is scanned, the D peak and G peak intensities of 100 points are obtained, the ID / IG of the 100 points is calculated, the maximum and minimum 25 ID / IGs are removed, and the average value of the remaining 50 points is the ID / IG of the material. The test instrument may be a Horiba LabRAM HR800 Raman spectrometer.
[0141] In this application, the powder compaction density of the negative electrode active material has a meaning known in the art and can be tested using methods known in the art. For example, referring to GB / T 24533-2009, it can be tested using an electronic pressure tester (e.g., UTM7305): a certain amount M of the powder sample to be tested is placed in a compaction mold (bottom area S), a different pressure (49000N can be used in this application) is set, the pressure is held for 30 seconds, the pressure is released, wait for 10 seconds, the thickness H after the powder has been compacted at this pressure is read by the device, and the compaction density at this pressure can be calculated. The compaction density of the negative electrode active material at this pressure is = M / (H*S).
[0142] In this application, the degree of graphitization of the material (e.g., the first negative electrode active material, the second negative electrode active material) has a meaning known in the art and may be tested using instruments and methods known in the art. For example, it can be tested using an X-ray diffractometer (e.g., a Bruker D8 Discover), and the test can be performed by obtaining the average interlayer spacing d002 of the C(002) crystal planes in the material crystal structure, referring to JIS K 0131-1996, JB / T 4220-2011, and then calculating the degree of graphitization from the formula g = (0.344 - d002) / (0.344 - 0.3354) × 100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal planes in the material crystal structure, expressed in nanometers (nm).
[0143] In this application, the OI of the materials (e.g., the first anode active material, the second anode active material) has a meaning known in the art and may be tested using instruments and methods known in the art. Based on the general rules for X-ray diffraction analysis and methods for measuring lattice parameters of graphite, JIS K 0131-1996, JB / T4220-2011, an X-ray diffraction spectrum can be obtained using an X-ray powder diffractometer (X'pert PRO), and the orientation index of the anode material can be calculated based on OI = C004 / C110. Here, C004 is the peak area of the characteristic diffraction peak of 004, and C110 is the peak area of the characteristic diffraction peak of 110.
[0144] In this application, the tap density of the material (e.g., the first negative electrode active material, the second negative electrode active material) has a meaning known in the art and may be measured using instruments and methods known in the art. For example, it can be measured using a powder tap density tester, referring to GB / T 5162-2006. The test equipment may be a Dandong Baite BT-301, with test parameters of an vibration frequency of 250 ± 15 times / min, an amplitude of 3 ± 0.2 mm, 5000 vibration cycles, and a graduated cylinder of 25 mL.
[0145] In this application, the volume distribution particle sizes Dv1, Dv10, Dv50, and Dv90 of the material (e.g., first negative electrode active material, second negative electrode active material, etc.) have meanings known in the art, and represent the particle sizes corresponding to when the cumulative volume distribution percentage of the material reaches 1%, 10%, 50%, and 90%, respectively, and can be measured with instruments and methods known in the art. For example, they may be measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern, UK.
[0146] In this application, the specific surface area of the material (e.g., the first negative electrode active material, the second negative electrode active material) has a meaning known in the art and may be measured using instruments and methods known in the art. For example, it can be tested using the nitrogen gas adsorption specific surface area analysis test method, referring to GB / T 19587-2017, and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, Inc., USA.
[0147] In this application, whether or not a coating layer exists on the surface of a material (e.g., a first negative electrode active material, a second negative electrode active material, etc.) can be determined by transmission electron microscopy.
[0148] In this application, the gram capacity of the material (e.g., the first negative electrode active material, the second negative electrode active material) has a meaning known in the art and may be tested using methods known in the art. An exemplary test method is as follows: A sample powder, conductive carbon black (Super P), and adhesive polyvinylidene fluoride (PVDF) are uniformly mixed with the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to prepare a slurry. The prepared slurry is applied to the surface of the copper foil of the negative electrode current collector and dried in an oven for use. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent. LiPF6 is then dissolved in the above organic solvent to a concentration of 1 mol / A CR2430 type button cell is assembled using a lithium metallic sheet as the counter electrode and a polyethylene (PE) film as the separator, in a glove box protected by argon gas and the electrolyte. After the resulting button cell is left to stand for 12 hours, it is discharged at 25°C at 0.05C to 0.005V with a constant current, left to stand for 10 minutes, discharged again at a constant current of 50μA to 0.005V, left to stand for 10 minutes, and discharged again at a constant current of 10μA to 0.005V, and the discharge capacity is recorded. The ratio of the discharge capacity to the sample mass is the gram capacity of the corresponding material (e.g., first negative electrode active material, second negative electrode active material, etc.).
[0149] The thickness of the negative electrode film layer has a known meaning in the art and can be tested using methods known in the art, for example, using a micrometer (e.g., Mitutoyo 293-100, accuracy 0.1 μm). The thickness range given in this application is the thickness range of the negative electrode film layer on one side of the negative electrode current collector. This application is satisfied if the thickness of the negative electrode film layer on either side of the negative electrode current collector is within the range given in this application.
[0150] It should be explained that the various parameter tests for the negative electrode active material or negative electrode film layer described above can be performed by sampling from secondary batteries manufactured according to the following steps.
[0151] The secondary battery is discharged (generally fully discharged for safety reasons), the battery is removed, the negative electrode plate is taken out, the negative electrode plate is immersed in dimethyl carbonate for a certain period of time (e.g., 2h to 10h), the negative electrode plate is then removed and dried at a certain temperature and time (e.g., 60°C, 4h or more), and the negative electrode plate is removed after drying. At this time, various parameters related to the negative electrode film layer, such as the compaction density, OI value, and thickness of the negative electrode film layer, can be sampled and tested from the dried negative electrode plate.
[0152] The dried negative electrode plate is fired at a constant temperature and time (e.g., 400°C for 2 hours or more), the negative electrode active material is sampled from any region of the fired negative electrode plate (the powder may be scraped off using a blade), the collected negative electrode active material is sieved (e.g., sieved with a 200-mesh sieve), and finally a sample is obtained that can be used to test each of the negative electrode active material parameters.
[0153] In this application, the first and second anode active materials mentioned above may be commercially available or manufactured by the following methods of this application.
[0154] In some embodiments, the first negative electrode active material can be manufactured according to the following method.
[0155] 1) Select petroleum-based needle-shaped coke raw materials, crush them, shape them, and classify them. 2) Heat treatment: Mix the process material and adhesive after step 1 in a ratio of (8-12):1 and perform granulation treatment. Raise the temperature of the granulation treatment to 600-700°C, bring it to a constant temperature, and perform the treatment for 8-12 hours. Then cool it for 5-10 hours to obtain intermediate product 1. 3) Graphitization: The intermediate product 1 from 2) is subjected to graphitization treatment, with a graphitization temperature of 2800-3200°C.
[0156] In step 2) above, the granulation process is carried out by raising the temperature to 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or within the range of any two of the aforementioned values, and then bringing it to a constant temperature. In step 2) above, the mass ratio is selected from the range of 8:1, 9:1, 10:1, 11:1, 12:1, or within the range of any two of the aforementioned values.
[0157] The graphitization temperature in step 3) above is within the range of 2800°C, 2900°C, 3000°C, 3100°C, 3200°C, or any two of the aforementioned values.
[0158] In some embodiments, the second negative electrode active material can be manufactured according to the following method.
[0159] 1) Select petroleum-based needle-shaped coke raw materials, crush them, shape them, and classify them. 2) Heat treatment: The process material and adhesive after step 1 are mixed in a mass ratio of (5-10):1 and granulated. The granulation process is heated to 600-700°C and then kept at a constant temperature for 8-12 hours, followed by cooling for 5-10 hours to obtain intermediate product 1. 3) Graphitization: Intermediate product 1 from 2) is subjected to graphitization treatment, with a graphitization temperature of 3000-3400°C to obtain intermediate product 2.
[0160] 4) Fusion coating and carbonization: Intermediate product 2 from step 3) is coated, and solid-liquid fusion is performed using a coating agent such as an organic carbon source, with the amount of coating agent added being 1-10% of the total mass of intermediate product 2, followed by carbonization, with a carbonization temperature of 1000-1200°C. The granulation treatment in step 2) above is heated to a constant temperature within the range of 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or any two of the aforementioned values. The mass ratio in step 2) above is selected from the range of 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any two of the aforementioned values.
[0161] The graphitization temperature in step 3) above is within the range of 3000°C, 3100°C, 3200°C, 3300°C, 3400°C, or any two of the aforementioned values.
[0162] The organic carbon source in step 4) above may include one or more of the following: coal pitch, petroleum pitch, phenolic resin, coconut shell, etc. The amount of coating added in step 4) above is in the range of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the total mass of intermediate product 2, or any two of the aforementioned values. The carbonization treatment temperature in step 4) above may be selected from the range of 1000°C, 1010°C, 1050°C, 1100°C, 1150°C, 1180°C, 1200°C, or any two of the aforementioned values.
[0163] [Positive electrode plate] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, the positive electrode film layer including a positive electrode active material according to the first embodiment of this application.
[0164] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of itself, and the positive electrode film layer is installed on one or both of the two opposing surfaces of the positive electrode current collector.
[0165] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer material substrate (for example, a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE)).
[0166] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may be a positive electrode active material known in the art and used in lithium-ion batteries. For example, the positive electrode active material may include at least one material from olivine-structured lithium-containing phosphates and lithium transition metal oxides and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may be used. These positive electrode active materials may be used individually or in combination of two or more. Here, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (Can be abbreviated as) LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (Can be abbreviated as) LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (Can be abbreviated as) LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 (Can be abbreviated as) LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 (Can be abbreviated as LiNi)), Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05It may contain, but is not limited to, at least one of O2) and its modified compounds. Examples of lithium-containing phosphates with an olivine structure include, but is not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (can be abbreviated as LFP)), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), composite materials of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and composite materials of lithium iron manganese phosphate and carbon.
[0167] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may be a positive electrode active material known in the art and used in lithium-ion batteries. For example, the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound.
[0168] Because batteries undergo lithium desorption and consumption during the charge-discharge process, the molar content of lithium will differ when the battery is discharged to different states. In the list of positive electrode materials in the embodiments of this application, the molar content of lithium represents the initial state of the material, i.e., before insertion. As the positive electrode material is used in a battery system and undergoes charge-discharge cycles, the molar content of lithium may change.
[0169] In the list of cathode materials in the embodiments of this application, the molar content of O is merely a theoretical value, and since lattice oxygen release causes a change in the molar content of oxygen, a fluctuation actually occurs in the molar content of O.
[0170] In some embodiments, the positive electrode film layer further selectively includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0171] In some embodiments, the cathode film layer selectively further comprises a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0172] In some embodiments, the positive electrode plate may be manufactured by the following method: Components for manufacturing the positive electrode plate, such as a positive electrode active material, a conductive agent, an adhesive, and any other component, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry. The positive electrode slurry is then applied onto a positive electrode current collector, and after processes such as drying and cold pressing, the positive electrode plate can be obtained.
[0173] [Electrolyte] The electrolyte plays a role in conducting ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and it may be selected according to the requirements. For example, the electrolyte can be a liquid, a gel, or an all-solid.
[0174] In some embodiments, an electrolyte solution is used as the electrolyte. The electrolyte solution comprises an electrolyte salt and a solvent.
[0175] In some embodiments, the electrolyte salt can be at least one selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0176] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0177] In some embodiments, the electrolyte further selectively includes additives. For example, the additives may include a negative electrode film-forming additive and a positive electrode film-forming additive, and may further include additives that can improve some of the battery's performance characteristics, such as an additive that improves the battery's overcharge performance, or an additive that improves the battery's high-temperature or low-temperature performance.
[0178] [Separator] In some embodiments, the battery cell further includes a separator. This application does not particularly limit the type of separator, and any known porous separator with excellent chemical and mechanical stability can be optionally selected and used.
[0179] In some embodiments, the material of the separator can be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multilayer composite film, and is not particularly limited. If the separator is a multilayer composite film, the materials of each layer may be the same or different, and are not particularly limited.
[0180] In some embodiments, the positive electrode plate, negative electrode plate, and separator can be manufactured into an electrode assembly by a winding process or a lamination process.
[0181] In some embodiments, the battery cell may include an outer casing. This casing may be used to package the electrode assembly and electrolyte.
[0182] In some embodiments, the battery cell casing can be a rigid case, such as a rigid plastic case, an aluminum case, or a steel case. The battery cell casing can also be a pouch, such as a bag-shaped pouch. The pouch material can be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0183] This application does not particularly limit the shape of the battery cell, and it can be cylindrical, rectangular, or any other shape. For example, Figure 4 shows a rectangular battery cell 5 as an example.
[0184] In some embodiments, referring to Figure 5, the casing may include a case 51 and a top cover assembly 53. Here, the case 51 may include a bottom plate and side plates connected to the bottom plate, and the bottom plate and side plates enclose a housing cavity. The case 51 has an opening that communicates with the housing cavity, and the top cover assembly 53 can cover the opening to seal the housing cavity. The positive electrode plate, negative electrode plate and separator may form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is packaged within the housing cavity. The electrolyte is impregnated into the electrode assembly 52. The number of electrode assemblies 52 included in the battery cell 5 may be one or more, and those skilled in the art can select according to their specific practical needs.
[0185] In some embodiments, battery cells can be assembled into a battery module, and the number of battery cells included in the battery module may be one or more, and the specific number can be selected by those skilled in the art depending on the application and capacity of the battery module.
[0186] Figure 6 shows an example of a battery module 4. Referring to Figure 6, in the battery module 4, the multiple battery cells 5 may be arranged sequentially along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, these multiple battery cells 5 may be fixed in place by fasteners.
[0187] Selectively, the battery module 4 may further include a housing having a housing space, in which a plurality of battery cells 5 are housed.
[0188] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, the specific number of which can be selected by those skilled in the art depending on the application and capacity of the battery pack.
[0189] Figures 7 and 8 show an example of a battery pack 1. Referring to Figures 7 and 8, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, the upper housing 2 being able to be covered by a lid on the lower housing 3, forming a sealed space for housing the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0190] Furthermore, a second aspect of this application further provides a power consumption device including a secondary battery according to this application. The secondary battery may be used as a power source for the power consumption device, or as an energy storage unit for the power consumption device. The power consumption device may include, but is not limited to, mobile devices (e.g., mobile phones, laptop computers, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0191] As the power consumption device, a battery cell, battery module, or battery pack can be selected based on the usage needs.
[0192] Figure 9 shows an example of a power consumption device. This power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the demand for high output and high energy density of the secondary battery in this power consumption device, a battery pack or battery module can be used.
[0193] Other examples of such devices include mobile phones, tablet computers, and laptop computers. These devices generally require a thin design and may utilize battery cells as a power source.
[0194] Examples Examples of the present application are described below. The examples described below are illustrative and are used solely for the purpose of interpreting this application and should not be understood as limitations thereon. Unless specific techniques or conditions are specified in the examples, they shall be carried out in accordance with the techniques or conditions described in the literature in the art or in accordance with the product description. Unless the manufacturer is specified, the reagents or equipment used are all commercially available and commonly used products.
[0195] Each of the materials used in the examples and comparative examples of this application may be commercially available and may be manufactured by the following process.
[0196] [Manufacturing of Material 1-1] (First negative electrode active material): 1) Select petroleum-based needle-shaped coke raw materials, crush them, shape them, and classify them. 2) Heat treatment: The process material and adhesive after step 1 are mixed in a mass ratio of 10:1 and granulated. The granulation treatment is heated to 650°C and kept at a constant temperature for 10 hours, then cooled for another 8 hours to obtain intermediate product 1. 3) Graphitization: The intermediate product 1 from 2) is subjected to graphitization treatment, and the graphitization temperature is 3000°C.
[0197] Here, the negative electrode active material 1-1 has a median Raman value of ID / IG R1 50is 0.08, and the powder compaction density at 49000N is 1.95g / cm 3 , the degree of graphitization is 94.5%, the powder OI is 4.8, and the volume distribution particle size D V 50 is 15μm, the volume distribution particle size D V 1 is 3.1μm, and the specific surface area is 2.0m 2 / g is satisfied.
[0198] [Production of Material 1-2 and Material 1-3] The difference from the production method of Material 1-1 lies in the graphitization temperature, and the details are as shown in Table 1.
[0199] [Table 1]
[0200] [Production of Material 2-1] (Second Negative Electrode Active Material): 1) A petroleum-based acicular coke raw material is selected, and subjected to crushing, shaping and classification treatments, 2) Heat treatment: The process material after step 1) and an adhesive are mixed at a mass ratio of 8:1 for granulation treatment, the granulation product is heated to 650°C and kept at a constant temperature for 10h, then further cooled for 8h to obtain Intermediate Product 1, 3) Graphitization: The Intermediate Product 1 from step 2) is subjected to graphitization treatment, with a graphitization temperature of 3200°C, to obtain Intermediate Product 2. 4) Fusion Coating and Carbonization: The Intermediate Product 2 from step 3) is subjected to coating treatment, a liquid-phase phenolic resin coating agent is used for solid-liquid fusion, the addition amount of the coating agent is 5% of the total mass of Intermediate Product 2, followed by carbonization treatment at a carbonization temperature of 1150°C, to obtain Negative Electrode Active Material 2-1.
[0201] Here, for Negative Electrode Active Material 2-1, the median value R1 of the Raman value ID / IG 50 is 0.25, and the powder compaction density at 49000N is 1.81g / cm 3 , the degree of graphitization is 93.5%, the powder OI is 3.3, and the volume distribution particle size D V 50 is 14.5μm, and the volume distribution particle size D V1 is 6.8 μm, and the specific surface area is 3.4 m². 2 The condition / g is met.
[0202] [Manufacturing of materials 2-2, 2-3, and 2-4]: The manufacturing method is similar to that of material 2-1, but the difference lies in the amount of coating agent added or the carbonization temperature, as detailed in Table 2.
[0203] [Table 2]
[0204] Example 1 Manufacturing of rechargeable batteries: 1. Manufacturing of the negative electrode plate The first negative electrode active material (material 1-1), the conductive agent carbon black (Super P), the thickening agent carboxymethylcellulose sodium, and the adhesive styrene-butadiene rubber were mixed thoroughly with an appropriate amount of deionized water as a solvent in a weight ratio of 96.4:1:1.2:1.4 to form the first negative electrode slurry.
[0205] The second negative electrode active material (material 2-1), the conductive agent carbon black (Super P), the thickening agent sodium carboxymethylcellulose, and the adhesive styrene-butadiene rubber were mixed thoroughly with an appropriate amount of deionized water as a solvent in a weight ratio of 96.4:1:1.2:1.4 to form the second negative electrode slurry.
[0206] The first negative electrode slurry was applied to the surface of the copper foil of the negative electrode current collector to form the lower region of the negative electrode film layer, and the second negative electrode slurry was applied to the first negative electrode film layer to form the upper region of the negative electrode film layer. After processes such as drying and cold pressing, a negative electrode plate was obtained. Here, the mass ratio of the first negative electrode slurry to the second negative electrode slurry was 6:4, and the compaction density of the negative electrode film layer was 1.6 g / cm³. 3 Therefore, the coating weight on one side of the negative electrode film layer is 8.6 mg / cm². 2 That is the case.
[0207] 2. Manufacturing of positive electrode plates Cathode active material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), a conductive agent (Super P), and an adhesive polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and the solvent N-methylpyrrolidone (NMP) was added and the mixture was thoroughly stirred to obtain a positive electrode slurry. The positive electrode slurry was then uniformly applied to the aluminum foil positive electrode current collector to form a positive electrode film layer, and after processes such as drying and cold pressing, a positive electrode plate was obtained.
[0208] 3. Manufacturing of electrolyte Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1. Subsequently, a well-dried lithium salt LiPF6 was dissolved in the mixed organic solvent at a rate of 1 mol / L to prepare the electrolyte, and then fluoroethylene carbonate (FEC) was added. The FEC content was 1 wt% of the total mass of the electrolyte.
[0209] 4. Separator Select polypropylene film.
[0210] 5. Manufacturing of rechargeable batteries: The positive electrode plate, separator, and negative electrode plate are stacked in order, with the separator positioned between the positive and negative electrode plates to act as an separator, and then wound up to obtain an electrode assembly. The electrode assembly is placed in an outer casing, the manufactured electrolyte is injected into the dried electrode assembly, and a secondary battery is obtained through processes such as vacuum packaging, settling, chemical conversion, and shaping.
[0211] Examples 2-3 The battery manufacturing methods in Examples 2 and 3 are similar to those in Example 1, but the difference lies in the selection of different materials 1-2 and 1-3 for the first negative electrode active material, as shown in Table 3.
[0212] Examples 4-6 The battery manufacturing methods of Examples 4 to 6 are similar to Example 1, with the difference that the second negative electrode active material selects different Material 2-2, Material 2-3, and Material 4, specifically as shown in Table 3.
[0213] Comparative Example 1 A secondary battery was assembled in the same manner as the manufacturing method of Example 1, with the difference that Material 2-1 was selected as the first negative electrode active material, and Material 1-1 was selected as the second negative electrode active material, specifically as shown in Table 3.
[0214] Comparative Example 2 A negative electrode active material (Material 1-1 and Material 2-1 mixed at a mass ratio of 6:4), a conductive agent carbon black (Super P), a thickener sodium carboxymethyl cellulose, and an adhesive styrene-butadiene rubber were thoroughly stirred and mixed at a weight ratio of 96.4:1:1.2:1.4 in an appropriate amount of solvent deionized water to form a negative electrode slurry, The negative electrode slurry was applied onto the surface of a negative electrode current collector copper foil to form a negative electrode film layer, and after undergoing processes such as drying and cold pressing, a negative electrode plate was obtained. Here, the compaction density of the negative electrode film layer is 1.6 g / cm 3 , and the single-side coating weight of the negative electrode film layer is 8.6 mg / cm 2 .
[0215] Comparative Example 3 A secondary battery was assembled in the same manner as the manufacturing method of Comparative Example 2, with the difference that the negative electrode active material only contains Material 1-1.
[0216] Comparative Example 4 A secondary battery was assembled in the same manner as the manufacturing method of Comparative Example 2, with the difference that the negative electrode active material only contains Material 2-1.
[0217] [Performance Test Method] All performance parameters related to all Examples and Comparative Examples are measured according to the following methods.
[0218] (1) Raman median R of the negative electrode active material in the negative electrode film layer 50 . The Raman spectra of each carbon material may be obtained using a laser confocal Raman spectrometer, with a laser wavelength of 532 nm. During testing, an appropriate amount of sample can be taken and its surface scanned in all directions. The scanning area is 100 μm × 100 μm, the step size is 2 μm, and the total number of scanning points is 2500. Raman spectra are obtained at different positions, and the corresponding Raman values ID / IG are obtained. The testing equipment can be a high-precision Renishaw laser confocal Raman spectrometer. The Raman values ID / IG obtained from the 2500 scanned points are arranged in ascending order and labeled as 1#, 2#, 3#, ..., 2500#. The Raman value ID / IG corresponding to the 50% rank of the number of scanning points (corresponding to 1250#) is defined as R50, and is also called the median value of the Raman values ID / IG. In this application, the median value of the Raman values ID / IG of the first negative electrode active material is defined as R1 50 It is noted that the median of the Raman values ID / IG of the second negative electrode active material is R2 50 (2) The gram volume of the ingredients.
[0219] The negative electrode active material, conductive agent Super P, and adhesive (PVDF) were uniformly mixed with the solvent NMP (N-methylpyrrolidone) in a mass ratio of 91.6:1.8:6.6 to produce a slurry. The produced slurry was applied to a copper foil current collector to produce a negative electrode film layer. After drying in an oven, it was cold-pressed to prepare it for use. The compaction density of the negative electrode film layer was 1.3 g / cm³. 3A metallic lithium sheet is used as the counter electrode, and a polyethylene (PE) film is used as the separator. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1. Then, LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, where the concentration of LiPF6 is 1 mol / L. The above parts are assembled into a CR2430 type button cell in a glove box protected by argon gas. After the obtained button cell is left to stand for 12 hours, a constant current discharge is performed with a current of 0.05C down to 0.005V, left to stand for 10 minutes, a constant current discharge is performed again with a current of 50 μA down to 0.005V, left to stand for 10 minutes, and a constant current discharge is performed again with a current of 10 μA down to 0.005V. The sum of the discharge capacities of the three discharges is the gram capacity of the material.
[0220] (3) Powder compaction density test The compaction density of the negative electrode active material has a meaning known in the art and may be tested using methods known in the art. For example, referring to GB / T 24533-2009, it can be tested using an electronic pressure tester (e.g., UTM7305): a certain amount M of the powder sample to be tested is placed in a compaction mold (bottom area S), a different pressure (49000N can be used in this application) is set, the pressure is held for 30 seconds, the pressure is released, wait for 10 seconds, the thickness H after the powder has been compacted at this pressure is read by the instrument, and the compaction density at this pressure can be calculated as follows: compaction density of the negative electrode active material at this pressure = M / (H*S).
[0221] (4) Thickness H of the single-sided negative electrode film layer. The thickness H of the single-sided negative electrode film layer can be measured using a micrometer. The thickness of the negative electrode film layer described in this application refers to the thickness of the negative electrode film layer for assembly of the battery after compaction by cold pressing.
[0222] (5) Degree of orientation of negative electrode active material OI. Based on JIS K 0131-1996 and JB / T4220-2011, which specify general rules for X-ray diffraction analysis and methods for measuring lattice parameters of graphite, an X-ray diffraction spectrum can be obtained using an X-ray powder diffractometer (X'pert PRO), and the orientation index of the negative electrode material can be calculated based on OI = C004 / C110, where C004 is the peak area of the characteristic diffraction peak of 004, and C110 is the peak area of the characteristic diffraction peak of 110.
[0223] (6) Mass energy density of the battery At 25°C, the battery cell was charged with a constant current of 0.33C up to 4.4V, then charged with a constant voltage until the current reached 0.05C, left to stand for 5 minutes, and then discharged with a constant current of 0.33C up to 2.8V to obtain the discharge capacity D0.
[0224] Mass energy density = D0 / mass of the secondary battery (unit: Wh / kg) In the formula, D0 is the measured discharge capacity of the battery core.
[0225] (7) Battery rate performance test. At 25°C, the secondary battery is charged with a constant current of 0.33C up to 4.4V, then charged with a constant voltage until the current drops to 0.05C, left to stand for 5 minutes, and then discharged with a constant current of 0.33C up to 2.8V. The actual capacity is recorded as C0.
[0226] Next, the secondary battery is charged sequentially at 0.5C0, 1.3C0, 2.0C0, 2.8C0, 3.5C0, 4.5C0, and 6.0C0 with a constant current until it reaches a negative electrode cutoff potential of 4.4V or 0V (the first one reached is used as the reference). After each charge is complete, it must be discharged to 2.8V at 1C0, with different charge multipliers for 10%, 20%, 30%, ..., 80% SOC (State of Charge). The negative electrode potential corresponding to the charging state (SOC) is recorded, and charge multiplier-negative electrode potential curves are drawn for different SOC states. After linear fitting, the charge multiplier corresponding to when the negative electrode potential is 0V in each SOC state is obtained. This charge multiplier is the charging window for this SOC state, denoted as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC, respectively. The charging time T from 10%SOC to 80%SOC of this secondary battery (assuming no lithium deposition occurs in the secondary battery) is calculated based on the formula (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC) × 10%, and the unit is min. The shorter this charging time, the better the rapid charging performance of the rechargeable battery.
[0227] The performance parameters for each example and comparative example are shown in Table 3.
[0228] [Table 3]
[0229] The following can be seen from the data in the table above. Examples 1-6 satisfy the design requirements of this application, and the battery can achieve both good rapid charging performance and relatively high energy density.
[0230] As can be seen from Comparative Example 1, its R1 50 R2 50 Because it is larger than this, it is outside the scope of this application, and the fast charging performance will be affected.
[0231] As can be seen from Comparative Example 2, the negative electrode active material is a physical mixture of material 1-1 and material 2-1, and the Raman median values of the negative electrode active material in the lower and upper regions tend to coincide. However, this does not conform to the design of the present application and also affects the rapid charging performance.
[0232] As can be seen from Comparative Examples 3 and 4, when the negative electrode active material contains only material 1-1 or material 2-1, the battery cannot achieve both good rapid charging performance and a relatively high energy density.
[0233] The embodiments described above are only a selection of embodiments of this application, not all embodiments. The detailed descriptions of the embodiments in this application are not intended to limit the scope of protection of this application, but merely represent selected embodiments of this application. All other embodiments derived from the embodiments in this application without the creative effort of a person skilled in the art are all within the scope of protection of this application. [Explanation of Symbols]
[0234] 1 Battery pack, 2 Upper housing, 3 Lower housing, 4 Battery module, 5 Battery cell, 51 Case, 52 Electrode assembly, 53 Top cover assembly, 10 Negative electrode plate, 101 Negative electrode current collector, 102 Negative electrode film layer, 102a Second surface, 102b First surface, 1021 Lower region, 1022 Upper region, 1023 Intermediate region, 200 First carbon-based material, 201 Outer region, 202 Inner region.
Claims
1. A secondary battery comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer comprises a lower region and an upper region, the lower region comprises a first negative electrode active material, the upper region comprises a second negative electrode active material, and the median of the Raman value ID / IG of the first negative electrode active material is R1 50 And, the median of the Raman values ID / IG of the second negative electrode active material is R2 50 In that case, R1 50 R2 50 A secondary battery characterized in that the first negative electrode active material is smaller than the second negative electrode active material, the degree of graphitization of the first negative electrode active material is greater than the degree of graphitization of the second negative electrode active material, and the volume distribution particle size Dv1 of the first negative electrode active material is smaller than the volume distribution particle size Dv1 of the second negative electrode active material.
2. The aforementioned R1 50 is 0.05 to 0.15, and / or R2 50 The secondary battery according to claim 1, characterized in that the value is 0.20 to 0.
40.
3. The aforementioned R1 50 is 0.05 to 0.1, and / or R2 50 The secondary battery according to claim 1, characterized in that the value is 0.25 to 0.
35.
4. The degree of graphitization of the first negative electrode active material is ≥ 92%, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the degree of graphitization of the second negative electrode active material is ≥ 91%.
5. The degree of graphitization of the first negative electrode active material is 93% to 95%, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the degree of graphitization of the second negative electrode active material is 92% to 94%.
6. The secondary battery according to any one of claims 1 to 3, characterized in that the powder compaction density of the first negative electrode active material is greater than the powder compaction density of the second negative electrode active material.
7. The first negative electrode active material has a powder compacted density of ≧1.95 g / cm when tested under a pressure of 49000 N 3 and / or The second negative electrode active material had a powder compaction density of 1.81 g / cm³ when tested at a pressure of 49,000 N. 3 ~1.87 g / cm 3 A secondary battery according to any one of claims 1 to 3, characterized in that it is the secondary battery described above.
8. The first negative electrode active material had a powder compaction density of 1.96 g / cm³ when tested at a pressure of 49,000 N. 3 ~1.99 g / cm 3 and / or, The second negative electrode active material had a powder compaction density of 1.82 g / cm³ when tested at a pressure of 49,000 N. 3 ~1.86 g / cm 3 A secondary battery according to any one of claims 1 to 3, characterized in that it is the secondary battery described above.
9. The secondary battery according to any one of claims 1 to 3, characterized in that the powder OI of the first negative electrode active material is greater than the powder OI of the second negative electrode active material.
10. The powder OI of the first negative electrode active material is 2.0 to 10.0, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the powder OI of the second negative electrode active material is 1.0 to 8.
0.
11. The powder OI of the first negative electrode active material is 4.0 to 8.0, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the powder OI of the second negative electrode active material is 2.5 to 5.
5.
12. The secondary battery according to any one of claims 1 to 3, characterized in that the tap density of the first negative electrode active material is smaller than the tap density of the second negative electrode active material.
13. The tap density of the first negative electrode active material is ≥ 0.8 g / cm³. 3 and / or, The specific surface area of the second negative electrode active material is 3.0 m². 2 / g ~ 4.3m 2 A secondary battery according to any one of claims 1 to 3, characterized in that it is / g.
14. The tap density of the first negative electrode active material is 0.85 g / cm³. 3 ~1.15 g / cm 3 and / or, The specific surface area of the second negative electrode active material is 3.2 m². 2 / g to 4.1m 2 A secondary battery according to any one of claims 1 to 3, characterized in that it is / g.
15. The volume distribution particle size Dv1 of the first negative electrode active material is 1.0 μm to 8.0 μm, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the volume distribution particle size Dv1 of the second negative electrode active material is 3.5 μm to 10.0 μm.
16. The volume distribution particle size Dv1 of the first negative electrode active material is 3.0 μm to 5.0 μm, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the volume distribution particle size Dv1 of the second negative electrode active material is 5.5 μm to 8.0 μm.
17. The secondary battery according to any one of claims 1 to 3, characterized in that the volume distribution particle size Dv50 of the first negative electrode active material is larger than the volume distribution particle size Dv50 of the second negative electrode active material.
18. The volume distribution particle size Dv50 of the first negative electrode active material is 10 μm to 20 μm, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the volume distribution particle size Dv50 of the second negative electrode active material is 10 μm to 20 μm.
19. The volume distribution particle size Dv50 of the first negative electrode active material is 14 μm to 16.5 μm, and / or The secondary battery according to any one of claims 1 to 3, characterized in that the volume distribution particle size Dv50 of the second negative electrode active material is 13 μm to 15.5 μm.
20. The particle size distribution of the first negative electrode active material (D V 90-D V 10) / D V 50 is the particle size distribution of the second negative electrode active material (D V 90-D V 10) / D V A secondary battery according to any one of claims 1 to 3, characterized in that it is greater than 50.
21. The particle size distribution of the first negative electrode active material (D V 90-D V 10) / D V 50 is ≤ 2.0 and / or, The particle size distribution of the second negative electrode active material (D V 90-D V 10) / D V A secondary battery according to any one of claims 1 to 3, characterized in that 50 is ≤ 1.
8.
22. The particle size distribution of the first negative electrode active material (D V 90-D V 10) / D V 50 is 1.2 to 1.8, and / or The particle size distribution of the second negative electrode active material (D V 90-D V 10) / D V A secondary battery according to any one of claims 1 to 3, characterized in that 50 is between 1.0 and 1.
6.
23. The secondary battery according to any one of claims 1 to 3, characterized in that the specific surface area of the first negative electrode active material is smaller than the specific surface area of the second negative electrode active material.
24. The specific surface area of the first negative electrode active material is 0.5 m². 2 / g to 3.0m 2 / g is and / or, The specific surface area of the second negative electrode active material is 2.5 m². 2 / g~4.4m 2 A secondary battery according to any one of claims 1 to 3, characterized in that it is / g.
25. The specific surface area of the first negative electrode active material is 1.0 m². 2 / g to 2.5m 2 / g and / or, The specific surface area of the second negative electrode active material is 3.0 m². 2 / g to 4.0m 2 A secondary battery according to any one of claims 1 to 3, characterized in that it is / g.
26. The first negative electrode active material is (1) D of the first negative electrode active material V The characteristic of 10 being 5 μm to 9 μm, (2) D of the first negative electrode active material V The characteristic is that 90 ≤ 30 μm, (3) D of the first negative electrode active material V The characteristic is that 99 ≤ 40 μm, (4) The secondary battery according to any one of claims 1 to 3, characterized in that it satisfies at least one of the following characteristics: (4) The gram capacity of the first negative electrode active material is 355 mAh / g to 365 mAh / g.
27. The first negative electrode active material is (1) D of the first negative electrode active material V The characteristic of 10 being 5.8 μm to 7.8 μm, (2) D of the first negative electrode active material V The characteristic of 90 is that it is between 20 μm and 30 μm, (3) D of the first negative electrode active material V The characteristic of 99 is that it is between 30 μm and 40 μm, (4) The secondary battery according to any one of claims 1 to 3, characterized in that it satisfies at least one of the following characteristics: (4) The gram capacity of the first negative electrode active material is 357 mAh / g to 363 mAh / g.
28. The second negative electrode active material is (1) D of the second negative electrode active material V The characteristic is that 10 is between 6 μm and 10.0 μm, (2) D of the second negative electrode active material V The characteristic is that 90 ≤ 30 μm, (3) D of the second negative electrode active material V The characteristic is that 99 ≤ 40 μm, (4) The second negative electrode active material has a gram capacity of 352 mAh / g to 362 mAh / g, (5) The secondary battery according to any one of claims 1 to 3, characterized in that at least one of the following is satisfied: (5) the surface of at least a portion of the second negative electrode active material has a carbon coating layer.
29. The second negative electrode active material is (1) D of the second negative electrode active material V The characteristic of 10 being 7.5 μm to 9.0 μm, (2) D of the second negative electrode active material V The characteristic of 90 is that it is between 20 μm and 30 μm, (3) D of the second negative electrode active material V The characteristic of 99 is that it is between 30 μm and 40 μm, (4) The second negative electrode active material has a gram capacity of 354 mAh / g to 360 mAh / g, (5) The secondary battery according to any one of claims 1 to 3, characterized in that at least one of the following is satisfied: (5) the surface of at least a portion of the second negative electrode active material has a carbon coating layer.
30. The secondary battery according to any one of claims 1 to 3, characterized in that the first negative electrode active material and / or the second negative electrode active material are both artificial graphite.
31. The compaction density of the negative electrode film layer is 1.25 g / cm³. 3 That is all, and / or, The coating weight per unit area of the negative electrode film layer is 0.075 mg / mm². 2 The secondary battery according to any one of claims 1 to 3, as described above.
32. The compaction density of the negative electrode film layer is 1.28 g / cm³. 3 ~1.65 g / cm 3 and / or, The coating weight per unit area of the negative electrode film layer is 0.08 mg / mm². 2 ~0.11mg / mm 2 A secondary battery according to any one of claims 1 to 3, characterized in that it is the secondary battery described above.
33. The power consumption device is characterized in that it includes a secondary battery as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Secondary battery and electric device
CN116964770A
Secondary battery, its manufacturing method and device equipped with the secondary battery
JP2022527147A
Secondary battery, its manufacturing method and device equipped with the secondary battery
JP2022527148A
Secondary battery, its manufacturing method and device equipped with the secondary battery
JP2022530744A